Atlas of Southeast Europe : geopolitics and history - Hötte, Hans H. A., 1922-2007. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2015)
This atlas offers a survey of the history of Southeast Europe from 1521 until 1699, from the first major land campaign undertaken by Sultan Süleyman I until the Treaty of Karlowitz at the end of the seventeenth century. It covers modern-day Hungary, Slovenia, Croatia, Serbia, Kosovo, Macedonia, Bosnia and Herzegovina, Montenegro, Romania (Walachia and Transylvania), Dalmatia, Greece and Cyprus.